PENGUATAN PERILAKU RAMAH LINGKUNGAN MELALUI ECOLITERASI BERBASIS PENDIDIKAN AGAMA ISLAM DI SB-SIKL, MALAYSIA - Riswanda Arneta Pertiwi; Rennanti Lunnadiyah Aprilia; Ulil Hanifah (Nusantara Hasana Journal, 2025)
Islamic Religious Education (PAI) has the potential to strengthen environmentally friendly behavior. This community engagement program was implemented at an SB (learning center) under the auspices of the Indonesian School of Kuala Lumpur (SIKL) in Kajang, Malaysia. The program aimed to build knowledge, attitudes, and practice (KAP) as a pathway to reinforcing pro-environmental behavior. A participatory, practice-based approach was used through four main interventions: foundational ecoliteracy lessons, a 3R (Reduce, Reuse, Recycle) recycling workshop, an educational mini-garden, and the “My Clean Environment” campaign. Evaluation combined pre–post knowledge tests (oral/written), a Likert 1–5 attitude survey (teacher observation/journaling), and program documentation. Four interventions were completed with high achievement: foundational lessons 87% (34/39 children demonstrated concept mastery); the recycling workshop 100% (all participants sorted waste and produced recycled crafts—photo frames and plant pots); the mini-garden 100% (15/15 children planted and cared for crops); and the campaign 100% participation with enthusiasm (poster products; visibly cleaner learning spaces). Knowledge gains were confirmed on several indicators: understanding of basic ecoliteracy concepts increased from 3 to 34 of 39 children; examples of pro-environmental behavior from 15 to 32 children; and recognition of environment-related Qur’anic verses/hadith from 2/15 to 15/15. Attitudes also trended positively (Likert Δ): cleanliness concern +1.0; enthusiasm for planting +3.5; discipline in waste disposal +0.5; responsibility for plant care +0.5; gratitude for God’s creation +1.5. Conclusion: Integrating PAI into ecoliteracy effectively strengthens children’s KAP. For comprehensive success, the follow-up plan includes implementing the postponed science experiment, standardizing measurement instruments, and establishing sustainability mechanisms (mini-garden upkeep, permanent 3R facilities, and post-program monitoring).